DAMPAK PANDEMI COVID-19 PADA RUMAH TANGGA PETANI/ NELAYAN/ BURUH DI INDONESIA (ANALISIS LANJUT STUDI DETERMINAN STATUS GIZI TAHUN 2020) - Yunita Diana Sari; Irlina Raswanti Irawan; Rika Rachmawati; Sudikno Sudikno; Elisa Diana Julianti (Persagi, 2022)
ABSTRACT The implementation of Large-Scale Social Restrictions (PSBB) policies which have implications for limiting community activities, including economic activities, educational activities, and other social activities. This activity restriction has an impact on the decline in the socio-economic conditions of the community, especially in vulnerable communities such as farmers/fishermen/laborers who do not have a fixed income. Therefore, the government, both at the National and regional levels, has issued various policies to deal with the spread of COVID-19 as well as policies to mitigate the social and economic impacts of this pandemic. The purpose of this analysis is to see the impact of the COVID-19 pandemic on households of farmers/fishermen/laborers who have children under five by conducting further analysis of the 2020 Nutritional Status Determinant Survey (SDSG) data. The number of respondents being analyzed is 6,866 households of farmers/fishermen/laborers. During the COVID-19 pandemic, the head of the family stated that they were economically less able to meet family needs (60.7%), had less income (80.9%), had more difficulty buying family food (63.8%), and had received social assistance from the government in the form of cash (57.4%). The consumption patterns for staple foods, where rice is still consumed by 99.6 percent of households, for the most consumed sources of protein, are fish (78.4%) and eggs (70.6%). Under-five children who did not access health services when sick were 46.7% for reason that they were not seriously ill so they did not need treatment (75.3%) and 17.9% did not or delaying the provision of basic immunization because of forgetting (18.2). Posyandu is the most visited health facility for basic immunization services and growth monitoring. Keywords: COVID-19 pandemic, social assistance, consumption patterns ABSTRAK Penerapan kebijakan Pembatasan Sosial Berskala Besar (PSBB) yang berimplikasi terhadap pembatasan aktivitas masyarakat, termasuk aktivitas ekonomi, aktivitas pendidikan, dan aktivitas sosial lainnya. Pembatasan aktivitas ini berdampak pada menurunnya kondisi sosial-ekonomi masyarakat, khususnya masyarakat rentan seperti petani,nelayan,buruh lainnya yang tidak berpenghasilan tetap. Oleh sebab itu, pemerintah, baik di tingkat pusat maupun daerah, mengeluarkan berbagai kebijakan untuk menanggulangi penyebaran COVID-19 serta kebijakan yang bersifat penanggulangan dampak sosial dan ekonomi akibat pandemi ini. Tujuan analisis ini untuk melihat dampak dari pandemi COVID-19 pada keluarga petani/nelayan/buruh yang mempunyai anak balita . menggunakan sumber data Survey Determinan Status Gizi (SDSG) 2020. Metode analisis adalah deskriptif analitik. Jumlah responden yang dianalisis sebanyak 6866 rumah tangga dengan pekerjaan kepala keluarga sebagai petani/nelayan/buruh. Selama pandemi COVID-19 kepala keluarga menyatakan kurang mampu secara ekonomi dalam memenuhi kebutuhan keluarga (60,7%), pendapat yang lebih sedikit (80,9%), lebih sulit untuk membeli bahan pangan keluarga (63,8%), pernah menerima bantuan sosial dari pemerintah berupa uang tunai (57,4%). Pola konsumsi makanan pokok rumah tangga adalah beras (99,6 persen), untuk sumber protein yang paling banyak dikonsumsi yaitu ikan (78,4%) dan telur (70,6%). Balita yang tidak mengakses ke pelayanan kesehatan ketika sakit46,7 persen dengan alasantidak sakit parah sehingga tidak perlu berobat (75,3%)ak/menunda pemberian imunisasi dasar 17,9 persen dengan alasan lupa (18,2%). Posyandu merupakan fasilitas kesehatan yang paling banyak dikunjungi untuk mendapatkan layanan imunisasi dasar dan pemantauan pertumbuhan. [Penel Gizi Makan 2022, 45(1):11-22]